Nano Resveratrol and Its Anticancer Activity - Deepika Balasubramanian; Agnishwar Girigoswami; Koyeli Girigoswami* (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
Cancer is one of the leading causes of death in the world, and there are various treatments for cancer. Although most of them cause adverse side effects, plant-based phytochemicals are studied for their anticancer properties to overcome these limitations. Among these, resveratrol has shown a prominent anticancer activity against different types of cancers such as ovarian, colorectal, breast, and liver cancers. Despite its pharmacological activities, resveratrol possesses some physiological and pharmacokinetic limitations including low bioavailability and poor solubility, and several other factors, and these limit the usage of resveratrol as an anticancer agent. These limitations of resveratrol can be rectified with the help of nanotechnology whereby resveratrol is nanoformulated with various types of nanoparticles including polymers, liposomes, dendrimers, and metals, which have different nanostructures such as spears, rods, and nanoflowers. Some of these have shown promising effects against the proliferation and migration of various types of cancer when used at low drug concentrations. Scientists have also observed the synergistic effects of nanoformulated resveratrol with other components. In this review, we discuss nano resveratrol and its anticancer activity against various types of cancer. Keywords: nanoformulation; bionanotechnology; anticancer; nano resveratrol; bioavailability *Corresponding author: Tel.: (+91)-9600060358 E-mail: koyelig@gmail.com